PENGARUH PERSEPSI HARGA DAN E-SERVICE QUALITY TERHADAP SUBSCRIPTION DECISION LAYANAN NETFLIX DI KALANGAN MAHASISWA FISIP UNIVERSITAS RIAU - Rahmadani, Alfhiyah; Othman, Lie (Komunitas Manajemen Kompetitif, 2025)
The development of new internet-based media has also changed people's lifestyle in fulfilling their needs and desires in finding information and even entertainment. Watching movies on subscription video on demand services has become one of the most popular forms of entertainment today, making conventional entertainment media begin to be abandoned. Netflix is one of the largest subscription-based streaming platforms in the world. The purpose of this study was to analyze the effect of perceived price and e-service quality on Netflix service subscription decisions among FISIP Riau University students. This research uses a quantitative approach by distributing questionnaires to FISIP Riau University students. The sample in this study consisted of 100 students of FISIP Riau University who subscribed to Netflix, which was determined using the Slovin formula. Sampling using non-probability techniques with purposive sampling method. The data obtained were analyzed using multiple linear regression. The final results of the study prove that perceived price and e-service quality affect the decision to subscribe to Netflix services among FISIP Riau University students. Keywords: Price Perception, E-service Quality, Subscription Decision